Contribution Rates of Psychological Skills in Learning Some Basic Handball Skills in Secondary School Students - Fadhiltailb Sabbar Aljanabi (Indian Journal of Forensic Medicine & Toxicology, 2020)
The research aims to identify ;the contribution rates of psychological skills (the ability to visualize, theability to relax, the ability to focus attention, the ability to face anxiety, self-confidence, motivation of sportsachievement) in learning the basic skills of handball (passing and receiving skill, skill jumping, skill Themain sample size was ( 65 secondary school students in the Republic of Iraq.The researcher connected thatthere is a relationship and contribution rates for psychological skills (ability to visualize, relaxation ability,ability to focus attention, ability).On the face of anxiety, th Self-Ge, sports achievement motivation) to learnsome basic handball skills (skill Altmrerwalastelam, Harrah's Altntit, skill correction).